PENINGKATAN PRODUKSI DAN KECERNAAN BAHAN KERING Centrosema pubescens DAN Pueraria phaseoloides OLEH PEMUPUKAN BATUAN FOSFAT DAN INOKULASI MVA - Dwi Retno Lukiwati (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
Centrosema pubescens (centro) and Pueraria phaseoloides (puero) are important forage legumes as protein and mineral sources for ruminant livestock in the tropics. However, most of the land that used for forage production is characterized by a low phosphorus content. As the high cost of superphosphate is a major limiting factor, a combination of rock phosphate (RP) fertilization and vesicular-arbuscular mycorrhizae (VAM) fungi inoculation maybe a promising technique. A field experiment was conducted in Bogor during 7 months, on a latosolic soil (low pH and low available Bray II extractable P) to evaluate the effects of RP fertilization and VAM inoculation and their interaction on dry matter (DM) production and in vitro dry matter digestibility. A completely randomized block design with 3 replicates was used. The main experiment consisted therein the combination of three factors as follows 1) legume species (centro, puero), 2) VAM inoculation (with, and without VAM inoculation), and 3) rock phosphate fertilization (0, 44, 87, 131, and 175 kg P ha-1). The period of defoliation was used as sub factor (defoliation I, II, and III). Results showed that DM production and DM digestibility of puero was significantly higher (P<0.05) compared to centro after defoliation. Dry matter digestibility of VAM inoculated puero was significantly higher (P<0.05) compared to uninoculated one. Rock phosphate fertilization significantly increased (P<0.05) DM production of VAM inoculated legume. Dry matter production was not significantly different (P>0.05) with or without VAM inoculation. When inoculated, rock phosphate fertilization increased DM production of legume. Success of VAM inoculation in the field affected by effectiveness of indigenous- VAM fungi or depending upon VAM inoculum potential.